Hubungan Pengetahuan Ibu dengan Kejadian Stunting di Desa Sena Kecamatan Batang Kuis Kabupaten Deli Serdang - Asnawi, Arifatul Aini; Putri, Dea Utami; Gianing, Dwene Nur; Pratiwi, Dwi Amanda; Hafizah, Rehana Qori; Rasyid, Abdul (Universitas Batanghari Jambi, 2024)
Stunting is a chronic nutritional problem that is recognized by having a body that is shorter than its age. Stunting occurs due to chronic lack of nutrition during the first 1000 days of life (HPK). The aim of this research is to determine the relationship between the level of maternal knowledge and the incidence of stunting in Sena Village, Batang Kuis District. This research is a quantitative research with a descriptive analytical design with a cross sectional approach. The results of this research prove that there is a relationship between maternal knowledge and the incidence of stunting in children under five in Sena Village.